PENGEMBANGAN KEMAMPUAN KOGNITIF MELALUI KEGITAN SAINS SEDRHANA KELOMPOK B1 DI TK KEMALA BHAYANGKARI 01 MATARAM - Intan Komalasari; I Nyoman Suarta; I Made Suwasa Astawa (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2020)
This research is motivated by the problem of cognitive development of children in Kemala Bhayangkari Kindergarten in group B1 children are still low and have difficulty distinguishing color changes that occur when mixed, teachers often have difficulty making children interested, focused, serious and concentrated when learning the introduction of science. Based on observations of simple science activities at TK Kemala Bhayangkari 01 Mataram, several problems were found, mainly in the field of cognitive development in terms of scientific activities and the various forms of results obtained were always below the expected standard so that the problem formulation of this research was how simple science activities could improve developmental abilities. cognitive abilities of children in Kemala Bhayangkari 01 Mataram Kindergarten in the 2018/2019 Academic Year. This study aims to determine children's simple science activities in improving cognitive development abilities in group B children at Kemala Bhayangkari 01 Kindergarten Mataram. The steps for implementing the activities carried out are as follows: 1, playing environment footing 2, stepping before playing 3, stepping during play 4, stepping after playing, and the last one is the final activity or closing activity. This research is a development research with three stages of development, each of which consists of planning, implementation, observation, and development analysis. Research data on children's cognitive abilities were collected using observation and documentation methods. The data obtained were analyzed using descriptive quantitative analysis method. Based on the results of the study showed that the steps of simple science activities in the first stage of development reached an average (34%), while in the second development stage it began to increase with an average value of 72%). And increased optimally in stage III with a percentage (87%). The results of this study are suggested to school administrators, teachers, and other researchers who can benefit from simple science activities. Thus, the results of this study can be concluded that simple science activities carried out with appropriate steps can develop the cognitive abilities of children in group B1 in TK Kemala Bhayangkari 01